Adaptability of a field isolate of Classical swine fever virus to PK-15 cells - AKSHAYA, R; RAMESH, A; LOGESH, K; SANGEETHA, R; VIJAYARANI, K; KUMANAN, K; GNANARAJ, P TENSINGH; RAJ, G DHINAKAR (The Indian Journal of Animal Sciences, 2020)
Classical swine fever (CSF) is an economically important pig disease affecting rural pig farming and vaccines are not freely available for control. In the present study an Indian isolate of CSF virus was passaged 75 times in PK-15 cells. At different passages, presence of virus was confirmed by Fluorescent Antibody Virus Neutralization (FAVN) test and Reverse Transcription-Polymerase Chain Reaction (RTPCR) for NS5B, E2 and 5-UTR genes. TCID50 titers were found to range between 4.00 and 8.97 at 10th and 75th passages respectively. Back passage and pathogenicity studies in susceptible pigs, the natural host, indicated that the virus was found to be attenuated following PK-15 passages and did not produce any clinical signs after 45th and 75th passages.